Transmission immunity in malaria: reflections on the underlying immune mechanisms during natural infections and following artificial immunization - Richard Carter; Kamini Mendis (Memorias do Instituto Oswaldo Cruz, 1992)
Malaria transmission-blocking immunity has been studied in natural malaria infections in man, during infections in animals and following artificial immunization of animals with sexual stage malaria parasites. Effective immunity, which prevents infectivity of a malarial infection to mosquitoes, has been observed under all of these circumstances. Two general types of effector mechanism have been identified. One is an antibody mediated mechanism which acts against the extracellular sexual stages of the parasite within the midgut of a blood feeding mosquito. The other is a cytokine mediated mechanism which inactivates the gametocytes of the parasites while in the circulation of the vertebrate host. Both effects have been observed during natural infections and following artificial immunization. The basis of induction of transmission-blocking immunity, including the nature of the memory for such immunity, however, may be very different in different host/parasite systems and during natural infection of following artificial immunization. Following artificial immunization a strong immune memory for transmission blocking immunity has been observed in animal systems. By contrast, following natural infections in man immune memory for transmission blocking immunity has been found to be weak and short lived if it occurs at all. It is suggested that the immunogens which induce natural transmission blocking immunity may be CD4+ independent.